EnVision: taking the pulse of our twin planet - Ghail,RC; Wilson,C; Galand,M; Hall,D; Cochrane,C; Mason,P; Helbert,J; MontMessin,F; Limaye,S; Patel,M; Stam,D; Wahlund,J-E; et al. (Experimental Astronomy: an international journal on astronomical instrumentation and data analysis, 2011)
EnVision is an ambitious but low-risk response to ESA’s call for a medium-size mission opportunity for a launch in 2022. Venus is the planet most similar to Earth in mass, bulk properties and orbital distance, but has evolved to become extremely hostile to life. EnVision’s 5-year mission objectives are to determine the nature of and rate of change caused by geological and atmospheric processes, to distinguish between competing theories about its evolution and to help predict the habitability of extrasolar planets. Three instrument suites will address specific surface, atmosphere and ionosphere science goals. The Surface Science Suite consists of a 2.2 m2 radar antenna with Interferometer, Radiometer and Altimeter operating modes, supported by a complementary IR surface emissivity mapper and an advanced accelerometer for orbit control and gravity mapping. This suite will determine topographic changes caused by volcanic, tectonic and atmospheric processes at rates as low as 1 mm a − 1. The Atmosphere Science Suite consists of a Doppler LIDAR for cloud top altitude, wind speed and mesospheric structure mapping, complemented by IR and UV spectrometers and a spectrophotopolarimeter, all designed to map the dynamic features and compositions of the clouds and middle atmosphere to identify the effects of volcanic and solar processes. The Ionosphere Science Suite uses a double Langmiur probe and vector magnetometer to understand the behaviour and long-term evolution of the ionosphere and induced magnetosphere. The suite also includes an interplanetary particle analyser to determine the delivery rate of water and other components to the atmosphere.